2015
DOI: 10.1186/s12882-015-0140-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of urinary kidney injury molecule-1 and interleukin-18 in the early post-burn period to predict acute kidney injury for various degrees of burn injury

Abstract: BackgroundBurn patients with AKI have a higher mortality, rapid diagnosis and early treatment of AKI are necessary. Recent studies have demonstrated that urinary KIM-1 and IL-18 are potential biomarkers of early-stage AKI, however, changes in urinary KIM-1 and IL-18 levels are unclear in patients with burns. The aim of our study was to determine whether combined KIM-1 and IL-18 are more sensitive than traditional markers in detecting kidney injury in patients with burns.MethodsNinety-five burn patients hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 25 publications
0
26
0
8
Order By: Relevance
“…SOD, catalase, MDA level of kidney tissue measured in UV-VIS Spectrophotometer by standard protocol [9,15,16]. IL-18 [17,18], KIM-1 [18,19], and cystatin-C [20] were measured by commercially available standard kit with standard protocol for kit literature by an ELISA plate reader.…”
Section: Biochemical Analysis By Semi Autoanalyzer Uv-vis Spectrophomentioning
confidence: 99%
“…SOD, catalase, MDA level of kidney tissue measured in UV-VIS Spectrophotometer by standard protocol [9,15,16]. IL-18 [17,18], KIM-1 [18,19], and cystatin-C [20] were measured by commercially available standard kit with standard protocol for kit literature by an ELISA plate reader.…”
Section: Biochemical Analysis By Semi Autoanalyzer Uv-vis Spectrophomentioning
confidence: 99%
“…A total of 12 studies could not be used for analysis of the prevalence of RRT, seven of which only reported on RRT patients (11,18,21,37,40,43,45), four of which were RCT studies (9, 10, 51, 52), and the remaining one of which were historical controls (44). Most of the 58 studies (41/60) were retrospective cohort studies, but 12 were prospective cohort studies (7,35,39,41,43,46,47,50,57,58,64,65), and 5 RCT studies (9, 10, 51, 52, 56). Moreover, we analysed the results of 41 studies that reported RRT mortality in burn patients ( Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT 22 prevented the expected increase in serum creatinine after HS [109]. More recently, several studies have examined this p38 pathway even further while simultaneously elucidating additional molecular mechanisms.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Severe traumatic injuries result in an influx of pro-inflammatory markers (e.g., cytokines, other signaling molecules) that have the potential to supplement clinical data to predict AKI and/or patient outcomes [21][22][23]. In trauma patients who initially survive their injuries, increased plasma levels of the cytokines interleukin-1 (IL-1), IL-6, IL-8, and monocyte chemoattractant protein 1 (MCP1) within the first 24 hours of admittance were associated with AKI occurrence [24].…”
Section: Aki and Traumamentioning
confidence: 99%